LP-13 Neuronal-derived iPSCs cell to evaluate neurotoxicity after 48 or 72 hours in high-through put screening format - V. Jahnke; F. Sabatier; J. Chaigne; M. Martin; R. Barbeau; L. Houssin; S. Raynal (Toxicology Letters, 2024)

Prevalence and polymorphism of a mussel transmissible cancer in Europe - Maurine Hammel; Alexis Simon; Christine Arbiol; Antonio Villalba; Erika A. V. Burioli; Jean‐François Pépin; Jean‐Baptiste Lamy; Abdellah Benabdelmouna; Ismael Bernard; Maryline Houssin; Guillaume M. Charrière; Delphine Destoumieux‐Garzon; et al. (Molecular Ecology, 2022)
Transmissible cancers are parasitic malignant cell lineages that have acquired the ability to infect new hosts from the same species, or sometimes related species. First described in dogs and Tasmanian devils, transmissible cancers were later discovered in some marine bivalves affected by a leukaemia‐like disease. In Mytilus mussels, two lineages of bivalve transmissible neoplasia (BTN) have been described to date (MtrBTN1 and MtrBTN2), both of which emerged in a Mytilus trossulus founder individual. Here, we performed extensive screening of genetic chimerism, a hallmark of transmissible cancer, by genotyping 106 single nucleotide polymorphisms of 5,907 European Mytilus mussels. Genetic analysis allowed us to simultaneously obtain the genotype of hosts – Mytilus edulis , M . galloprovincialis or hybrids – and the genotype of tumours of heavily infected individuals. In addition, a subset of 222 individuals were systematically genotyped and analysed by histology to screen for possible nontransmissible cancers. We detected MtrBTN2 at low prevalence in M . edulis , and also in M . galloprovincialis and hybrids although at a much lower prevalence. No MtrBTN1 or new BTN were found, but eight individuals with nontransmissible neoplasia were observed at a single polluted site on the same sampling date. We observed a diversity of MtrBTN2 genotypes that appeared more introgressed or more ancestral than MtrBTN1 and reference healthy M . trossulus individuals. The observed polymorphism is probably due to somatic null alleles caused by structural variations or point mutations in primer‐binding sites leading to enhanced detection of the host alleles. Despite low prevalence, two sublineages divergent by 10% fixed somatic null alleles and one nonsynonymous mtCOI (mitochondrial cytochrome oxidase I) substitution are cospreading in the same geographical area, suggesting a complex diversification of MtrBTN2 since its emergence and host species shift.

First description of a mortality event in adult Pacific oysters in Italy associated with infection by a Tenacibaculum soleae strain - E A V Burioli; K Varello; S Trancart; E Bozzetta; A Gorla; M Prearo; M Houssin (Journal of Fish Diseases, 2018)
Summer mortality episodes in adult Pacific oysters have been described since the 1950s in various farming areas. Starting in 2012, a recrudescence of mortalities in commercial‐sized oysters was first observed in France and then in Italy, with seasonality extension and translation later in the year. Moribund individuals collected during an event in Italy in December 2014 showed yellowish lesions of the mantle and adductor muscle. Histological examination revealed filamentous bacteria associated with necrotic areas. Quantitative PCR s targeting Os HV ‐1 and Vibrio aestuarianus detected only high loads of the pathogenic bacteria in tissues of symptomatic individuals. A lower diversity of the hemolymph microbiota was also evidenced in moribund individuals, with a predominance of Vibrio and Arcobacter species. A strain of Flavobacteriaceae was isolated from all the symptomatic individuals. Sequence analysis of the 16S rRNA gene identified the strain as Tenacibaculum soleae . When strain pathogenicity was tested by injection in adult individuals, it induced mortality rates of up to 45%, even in the absence of V. aestuarianus . As mortality occurred only 11 days post‐infection, further investigation is needed to determine its effective virulence in natural conditions. This is the first description of a Tenacibaculum strain associated with bivalve mortalities.

Cloning of AFLP markers linked to resistance to Peronosclerospora sorghi in maize - H. Agrama; S. Houssin; M. Tarek (Molecular Genetics and Genomics, 2002)